Staphylococcus epidermidis biofilms are resistant to phage infection due to the protective effect of the biofilm matrix - Melo, Luís Daniel Rodrigues (2014)
EMBO Conference on Viruses of Microbes III: Structure and Function - from Molecules to Communities (Programme and Abstract Book)